Idiom-Translating Strategies in "Perahu Kertas” Novel by Dee Lestrari Translated by Tiffany Tsao - Utami, Silvia; Karnedi, Karnedi; Vivian, Vivian (JOLADU: Journal of Language Education, 2023)
The rapid development of novel translations causes shifts in the word structure such as idioms where the meaning cannot be translated literally; thus, some strategies are needed in translating these idioms from the source language to the target language. This study aimed at identifying and analyzing the strategies used in idiom translating and the most dominant strategy used in “Perahu Kertas” novel by Dee Lestari to the English translated version translated by Tiffany Tsao. The method used in this research was descriptive qualitative where the collected data later be analyzed according to Baker’s idiom translation. The results showed that 9 translations using similar meaning and form strategy, 8 translations using similar meaning and dissimilar form, 23 translations by paraphrasing, and 8 translations by omission. The paraphrasing was the most used strategy in this translation with a percentage of 48%.